Effectiveness and safety of 1L PEG-ASC preparation for colonoscopy in patients with inflammatory bowel diseases. Issue 9 (September 2021) - Maida, M.; Morreale, G.C.; Sferrazza, S.; Sinagra, E.; Scalisi, G.; Vitello, A.; Vettori, G.; Rossi, F.; Catarella, D.; Di Bartolo, C.E.; Schillaci, D.; Raimondo, D.; et al.
Abstract: Introduction: The effectiveness of bowel cleansing is a key element for high-quality colonoscopy. Recently, a 1 L polyethylene glycol plus ascorbate (PEG-ASC) solution has been introduced, but effectiveness and safety of this preparation have not been assessed in IBD patients. This study aims to evaluate effectiveness and safety of 1 L PEG-ASC solution in patients with IBD compared to controls. Methods: We retrospectively analysed prospectively collected data on a cohort of 411 patients performing a colonoscopy after preparation with 1 L PEG-ASC, consecutively enrolled in 5 Italian centres. Results: Overall, 185/411 (45%) were patients with IBD and 226/411 (55%) served as controls. A significantly higher cleansing success was achieved in IBD patients (92.9% vs 85.4%, p = 0.02). The multiple regression model showed that presence of IBD (OR=2.514, 95%CI=1.165–5.426; P = 0.019), lower age (OR=0.981, 95%CI=0.967–0.996; P = 0.014), split preparation (OR=2.430, 95%CI=1.076–5.492; P = 0.033), absence of diabetes (OR=2.848, 95%CI=1.228–6.605; P = 0.015), and of chronic constipation (OR=3.350, 95%CI=1.429–7.852; P = 0.005), were independently associated with cleansing success. The number of treatment-emergent adverse events (TEAEs) (51 vs 62%, p = 0.821), and of patients with TEAEs (22.2% vs 21.2%, p = 0.821), were similar in IBD patients and in controls, respectively. Conclusions: Results from this study support the effectiveness and safety of 1 L PEG-ASC solution in IBD patients, which may improve the definition of endoscopic outcomes both in Crohn's disease and ulcerative colitis.